A prospective study of single dose preoperative antibiotic cover in clean elective surgical cases- a single center study - Subramaniyan, Siddhartha Gowthaman; Gunasekaran, Prabhu; Manickam, Ramanathan (International Surgery Journal, 2020)
Background: Surgical site infection (SSI) is the third most common nosocomial infections occurring worldwide, thus leading to increasing cost, mortality and morbidity. The main objective was to know the incidence of SSI in clean surgical procedures carried out in the institute of MGMCRI and to determine various pathogens causing SSI. Methods: This was a prospective observational study done on 100 patients in Department of General Surgery in MGMCRI, Puducherry from June 2015 to August 2017 who underwent clean surgical procedure. Preoperatively single done of injection cefazolin 1gm intravenous preparation was given 30 minus before the skin incision and patient were observed and followed up meticulously for the incidence of SSI and to determine the bacterial flora in the event of SSI. Results: In our study a total of 100 patients were included. In our study a total of three out of 100 patients developed SSI which was around 3%.Out of the 3 patients who had SSI all were a male which is around 4.6% in our study. In relation to the distribution based on the age group more than 50 year of the age are most frequently associated with SSI in our study. The bacterial flora includes staphylococcus aureus which was isolated from one patient and Klebsiella pneumonia isolated from two patients who had surgical site infections. Conclusions: This study concludes that single dose pre-operative antibiotic has advantage in prevention of SSI and it is cost effective for patient.